2011
DOI: 10.1007/s11248-011-9515-9
|View full text |Cite
|
Sign up to set email alerts
|

Feral genetically modified herbicide tolerant oilseed rape from seed import spills: are concerns scientifically justified?

Abstract: Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.1 | P a g e KEYWORDSGenetically modified oilseed rape, herbicide tolerance, seed spillage, ferality, persistence, invasiveness, coexistence, introgression 2 | P a g e ABSTRACTOne of the concerns surrounding the import (for food and feed uses or processing) of genetically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 128 publications
0
75
0
Order By: Relevance
“…The EFSA GMO Panel previously evaluated the plant-to-plant gene transfer from feral oilseed rape GT73 plants to cross-compatible plant species and the potential environmental consequences of such gene transfer (EFSA, 2004(EFSA, , 2009c Newly published data since the adoption of the 2004 EFSA GMO Panel Scientific Opinion confirm that seed dispersal is likely to occur and to result in feral GMHT oilseed rape plants in regions where GMHT oilseed rape is cultivated and/or transported (reviewed by Devos et al, 2012). In regions where GMHT oilseed rape is widely grown such as western Canada and the USA, monitoring surveys revealed the widespread occurrence of feral GMHT oilseed rape plants along field margins of agricultural fields, as well as along transportation routes (such as road verges and railway lines).…”
Section: It Concluded That: "In the Very Unlikely Event That Such A Hmentioning
confidence: 99%
“…The EFSA GMO Panel previously evaluated the plant-to-plant gene transfer from feral oilseed rape GT73 plants to cross-compatible plant species and the potential environmental consequences of such gene transfer (EFSA, 2004(EFSA, , 2009c Newly published data since the adoption of the 2004 EFSA GMO Panel Scientific Opinion confirm that seed dispersal is likely to occur and to result in feral GMHT oilseed rape plants in regions where GMHT oilseed rape is cultivated and/or transported (reviewed by Devos et al, 2012). In regions where GMHT oilseed rape is widely grown such as western Canada and the USA, monitoring surveys revealed the widespread occurrence of feral GMHT oilseed rape plants along field margins of agricultural fields, as well as along transportation routes (such as road verges and railway lines).…”
Section: It Concluded That: "In the Very Unlikely Event That Such A Hmentioning
confidence: 99%
“…Demographic studies of feral oilseed rape have shown the ability of oilseed rape to establish selfperpetuating populations outside agricultural areas, mainly in semi-natural and ruderal habitats in different countries (reviewed by Devos et al, 2012). Oilseed rape is generally regarded as an opportunistic species and can take advantage of disturbed sites due to its potential to germinate and capture resources rapidly.…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%
“…The review of Devos et al (2012) on feral GM herbicide tolerant oilseed rape from seed import spills raises the question if concerns about environmental damages are scientifically justified. The question and the attempt of an answer fail to separate scientific analysis from evaluation.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%